Pembelajaran Berbasis Masalah untuk Meningkatkan Kemampuan Berpikir Kreatif dan Self-Concept Siswa SMP - Ratni Purwasih; Ratna Sariningsih (Didaktik Matematika, 2017)
This research is based on the lack of students ability in mathematical creative thinking and self concept. For that reason, this study aims to improve the students ability of mathematical creative thinking and self-concept through problem-based learning. Using Quasi Experiment method and nonequivalent control group design, this study is included into experimental research. The population of this research is the seventh graders of Junior High School in the district of Cimahi, West Java, Indonesia, and the sampling technique is purposive sampling, with one experimental group which is mathematical learning using problem-based learning (PBM) and one control group which is mathematical learning using conventional onewiththe number of samples in this study were 74 students. The hypothesis test his study is done by using parametric and nonparametric test (t-test and Mann-Whitney). The results showed that mathematical creative thinking and self-concept ability of students who use problem-based learning is better than students who receive conventional learning. Then, the increase of ability and creative thinking of students who use problem-based learning is better than those who receive the conventional learning and their self-concept is classified as being medium